KEY ISSUES IN THE AUDIT OF FINANCIAL STATEMENTS IN UZBEKISTAN - Isroil Ismoilovich Meliev (European Science Publishing, 2026)
This article is devoted to the features of conducting an audit of financial statements prepared in accordance with international standards in Uzbekistan, in which the relevance of studying this topic, the level of study, the features of organizing an audit of financial statements prepared in accordance with international standards, the opportunities achieved in the implementation of IFRS and AAS in practice, issues to be studied in the process of auditing transactions made after the date of preparation of financial statements, the differences in the audit of financial statements prepared using parallel accounting (conversion) and transformation methods, and practical recommendations for improving this process are formulated.
Keywords: Financial statement audit, international auditing standards, international financial reporting standards, financial reporting standards, fraud, misrepresentation of financial statements, errors and omissions in financial statements, reliability of financial statements, users of financial statements, parallel accounting (conversion) method, transformation method.